Blood Changes and Enhanced Thromboxane and 6-Keto Prostaglandin F1α Production in Experimental Acute Plasmodium Bergei Infection in Hamsters - Essien, E M; Arnout, J; Deckmyn, H; Vermylen, J; Verstraete, M (Thrombosis and Haemostasis, 1984)
Golden hamsters inoculated intraperitoneally with Plasmodium bergei infected mouse blood regularly developed P. bergei parasitaemia. This was associated with progressive thrombocytopenia and leucocytosis as the degree of parasitaemia increased with time. When infected whole blood was stimulated with collagen, significantly enhanced thromboxane B2 (TXB2) production per platelet was seen. 6-keto prostaglandin (PG) F1α formation in the same system increased from the sixth infection day onwards and correlated with the relative leukocytosis. The production of 6-keto PGF1α by aorta rings was significantly higher during the 4-7th days postinoculation. The increase in thromboxane production however was much more important than that of 6-keto PGF1α and it therefore is concluded that P. bergei parasitaemia in hamsters tilts the haemostatic balance towards the platelet hyperaggregability that has also been described in P. falciparum infection in man.
Keywords: P. bergei parasitaemia; Platelets; Thromboxane; Prostacyclin; Whole blood